(untitled) (Advances in Military Technology, 2018)
A flight recorder, commonly known as a black box, is considered the most important witness in the investigation of air accidents. Flight recorders have been considered important parts of onboard equipment for both military and civilian aircraft all over the world already from 1950s. They are used not only for flight evaluation after an unexpected event, but also for a pilot training, pilot skills assessment, diagnostics of on ‐ board systems, and evaluation of aircraft systems as a whole. Thus, these flight recorders contribute to high aircraft reliability and aviation operation safety. This article focuses on Automatic Deployable Flight Recorders (ADFR), currently not often used in the military or civilian aircraft. ADFRs are mainly used for aircraft that fly over vast water areas as classic concept recorders were hard to find when the aircraft crashed into water. This deployable recorder is a reliable flight safety system used e.g. in US Navy F/A ‐ 18 multirole combat jets. In addition, creation of this article was inspired by the change in ICAO Standards and Recommended Practices for Operation of Aircraft, implemented in July 2016 in the tenth edition of ICAO Annex 6.